Immersive Learning Environment Model: Narratives as a Strategy for the Development of Intercultural Competences in Digital Environments - García Gutiérrez, Zaily del Pilar; Agudelo Franco, Maryuri; Fronseca Franco, Ingrid Patricia; Perdomo Vanegas, William Leonardo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This article presents the results of the first phase of the research project “Model and Laboratory for Inclusive and Intercultural Teaching Based on Universal Design for Learning and Immersive Environments.” The study evaluated the effectiveness of narratives as a strategy to design inclusive learning experiences, enhance student learning, and foster interculturality in digital environments. Data were collected from university students using a validated questionnaire and analyzed with a mixed-methods approach. The results highlight narratives, supported by social media, as key tools for personalizing learning, overcoming accessibility barriers, and connecting content to students’ sociocultural contexts, promoting equity in the Model design.